2020
DOI: 10.3389/fimmu.2020.01463
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Inhibition Delays Retinal Degeneration Due to MerTK Phagocytosis Receptor Deficiency

Abstract: Retinitis Pigmentosa (RP) is a group of inherited retinal diseases characterized by progressive loss of rod followed by cone photoreceptors. An especially early onset form of RP with blindness in teenage years is caused by mutations in mertk, the gene encoding the clearance phagocytosis receptor Mer tyrosine kinase (MerTK). The cause for blindness in mutant MerTK-associated RP (mutMerTK-RP) is the failure of retinal pigment epithelial cells in diurnal phagocytosis of spent photoreceptor outer segment debris. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 63 publications
3
46
1
Order By: Relevance
“…With more advanced disease, and greater levels of photoreceptor death, more microglia would be expected to accumulate within the subretinal space. Indeed, several studies have shown increasing numbers of Iba1 positive cells (likely microglia or subretinal macrophages) in the subretinal space from postnatal 14 (He et al, 2019 ; Lew et al, 2020 ). However, comparison of dorsal and ventral retinae with equivalent levels of surviving photoreceptors (i.e., 12 month old dorsal retina compared with 2 month old ventral retina), shows that the ventral retina has a disproportionate number of microglia for the equivalent photoreceptor death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With more advanced disease, and greater levels of photoreceptor death, more microglia would be expected to accumulate within the subretinal space. Indeed, several studies have shown increasing numbers of Iba1 positive cells (likely microglia or subretinal macrophages) in the subretinal space from postnatal 14 (He et al, 2019 ; Lew et al, 2020 ). However, comparison of dorsal and ventral retinae with equivalent levels of surviving photoreceptors (i.e., 12 month old dorsal retina compared with 2 month old ventral retina), shows that the ventral retina has a disproportionate number of microglia for the equivalent photoreceptor death.…”
Section: Discussionmentioning
confidence: 99%
“…Microglia and other mononuclear phagocytes are known to release a range of inflammatory cytokines, and their sheer number could exert cytotoxic effects on neighboring photoreceptors. Indeed, a recent study showed increased expression of the chemokine Ccl5 from postnatal 14 in the RCS rat retina and suppression of microglia activity with tamoxifen or the liposome clodronate reduced photoreceptor death (Lew et al, 2020 ). Moreover, there is some evidence that microglia migrate into the subretinal space of the RCS or mertk-/- mouse in response to photoreceptor death (Kohno et al, 2015 ; Lew et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoreceptor degeneration initiated by an inflammatory network has been well documented, and the roles of microglia have been characterized in such models, especially by suppressing microglial activity through drug administration. 6,7,34,35 However, we believe that these models have limited utility for examining the primary effects of activated microglia in healthy retinas. In this study, we found evidence of Edn2 and Lif transcriptional activation in Cx3cr1-RasV12 retinas.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of microglia activation using tamoxifen or a combination of tamoxifen with liposomal clodronate increases the viability and function of photoreceptor cells in the rat model mutMerTK-RP [ 116 ].…”
Section: Therapeutic Approaches To Reduce Inflammation and Cell Dementioning
confidence: 99%